The relationship between noise with stress and sleep disturbances among manufacturing workers - Razak, Nuaim; Rasdi, Irniza; Zainal Abidin, Emilia; Syed Ismail, Sharifah Norkhadijah (Environmental and Occupational Health Society, 2015)
Objective: Noise can pose various detrimental effects that may put workers at high risk for occupational injuries and detrimental organisational consequences. This study aims to determine the effects of occupational noise exposure levels to psychological stress and sleep disturbance among manufacturing workers in Selangor.